Hardware and circuit design of a vibrational cleaner - Chin, Fhong Soon; Kok, Tung Thong; Kian, Sek Tee; Nayan, Nafarizal; Ahmad, Mohd Khairul; Nordin, Anis Nurashikin (Institute of Physics Publishing, 2016)
Microtissue can be grown on soft substrates of hydrogel or liquid crystal gel. These gels are adherent to the microtissues and they may interfere fluorescence imaging as background noise due to their absorbance property. A microfluidic vibrational cleaner with polydimethylsiloxane (PDMS) microfluidic chip platform was proposed and developed to remove the residual gel of liquid crystal adhered to the microtissues. The microtissues were placed in a microfluidic chip attaching to a microfluidic vibrational platform. In the system design, two motorised vibrators vibrating attached to a microfluidic platform and generating vibration signals at 148 Hz and 0.89 Grms to clean the microtissues. The acceleration of the vibration increased gradually from 0 to 0.96 Grms when the duty cycle of PWM pulses increased from 50 - 90%. It dropped slightly to 0.89 Grms at 100% duty cycle. Irrigation water valve was designed to control the fluid flow from water pump during cleaning process. Water pumps were included to flush the channels of the microfluidic device. The signals in controlling the pump, motor and valve were linearly proportional to the duty cycles of the pulse width modulation signals generated from a microcontroller.